The effect of citrates and sulfates of different metals on the biomass composition of medicinal mushroom Trametes versicolor (L.) Lloyd (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
A comparative study has been carried out on the impact of citrate and sulfate of zinc and manganese on the biomass composition of mycelium of medicinal mushroom Trametes versicolor 353 cultivated in a liquid media. It was demonstrated that sulfates and citrates of studied metals have different effects on the mycelial growth and some biochemical parameters. Sulfates and citrates of these metals influence to different degrees on the amount of some amino acids in the mycelium of T. versicolor 353. Also citrates of both metals decrease amount of cis-linoleic acid (C18:2) relative to the control medium and medium with sulfate of appropriate metals.
Keywords: Trametes versicolor, citrate, sulfate, zinc, manganese, amino acids, fatty acids.